Knowledge of the relatives of children with diabetes mellitus 1 attended at a referral center (Research, Society and Development, 2018)
Introduction: Type 1 DM is one of the most common chronic diseases of childhood, requires special care and demands of patients and caregivers behavior that suit the demands of treatment, seeking a control of the disease, adherence to therapy and knowledge of what involves the disease. Objective: To identify the level of knowledge of the relatives of children and adolescents with type 1 DM, attended at a referral center in DM in southern Brazil. Methods: A transversal study with a quantitative approach performed with 62 family members of children and adolescents diagnosed with DM1, who answered two questionnaires, one with sociodemographic variables and other about the knowledge of the disease. Results: The study identified a good knowledge about the disease, with a significant difference (p = 0.005) when compared to the level of education of the participants. Of the total, 25% of those evaluated were below the recommended level in the test. Conclusion: Those guardians have a good knowledge about the disease, however other factors imply in the not controlling of the DM. It is important to highlight the importance of professionals be prepared to continue to carry out educational activities that aim at the individuality of each family attended.